Effects of enzymatically hydrolyzed fish by-products in diet of juvenile rainbow trout (Oncorhynchus mykiss) - Jinho Bae; Abul Kalam Azad; Seonghun Won; Ali Hamidoghli; Minji Seong; Sungchul C. Bai (Fisheries and Aquatic Sciences, 2019)
Abstract Five experimental diets were formulated to evaluate the effects of dietary enzymatically hydrolyzed tuna by-product on growth, non-specific immune responses, and hematology of juvenile rainbow trout (Oncorhynchus mykiss). A basal diet with 50% of fishmeal was used as control (CON) and four other diets replaced 12.5% (TBB12.5), 25% (TBB25), 37.5% (TBB37.5), and 50% (TBB50) of fish meal in the CON diet. Juvenile rainbow trout (4.87 ± 0.05 g) were randomly distributed into 15 tanks (50 L) and fed 3–4% of wet body weight two times a day. At the end of 7 weeks of feeding trial, weight gain, specific growth rate, feed efficiency, and protein efficiency ratio of fish fed CON diet were significantly higher than those of fish fed TB50 diet (P < 0.05). But there were no significant differences among fish fed CON, TBB12.5, TBB25, and TBB37.5 diets (P > 0.05). There were no significant differences in GPT levels among fish fed CON, TBB12.5, TBB25, and TBB37.5 diets. Also, there were no significant differences in lysozyme, superoxide dismutase, glucose, and total protein levels in all experimental diet (P > 0.05). The broken-line analysis indicated that the minimum dietary level of enzymatically hydrolyzed tuna by-product to replace fishmeal could be 29.7% in rainbow trout. These results indicated that the optimum level of dietary enzymatically hydrolyzed tuna by-product could replace greater than 29.7% but less than 37.5% of fishmeal in juvenile rainbow trout diet.